2003
DOI: 10.1046/j.1365-2265.2003.01907.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by progestogens of the effects of oestrogen on hepatic endocrine function in postmenopausal women

Abstract: Oestrogen effects on IGF-I, GHBP and SHBG are dependent on the route of administration with progestogens having variable effects. Among the progestogen types, norethisterone, the most androgenic, had the greatest effect, particularly on IGF-I. Progestogens modulate the effects of oestrogen on hepatic endocrine function in relation to their intrinsic androgenic properties. The modulatory effects of progestogens on IGF-I during oestrogen therapy may have long-term implications for lean body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
23
1
1
Order By: Relevance
“…At least the potentially stimulating effect of the synthetic progesterone on collagen turnover is overruled by the ethinyl estradiol administration. In support, exogenous progestogens have been shown to enhance the IGF-I concentration (50), whereas in the present study IGF-I was reduced after OC administration, which underlines the dominating effect of estradiol compared with the effect of progestogens.…”
Section: Effect Of Oc On Sex Hormonal Concentrationscontrasting
confidence: 48%
“…At least the potentially stimulating effect of the synthetic progesterone on collagen turnover is overruled by the ethinyl estradiol administration. In support, exogenous progestogens have been shown to enhance the IGF-I concentration (50), whereas in the present study IGF-I was reduced after OC administration, which underlines the dominating effect of estradiol compared with the effect of progestogens.…”
Section: Effect Of Oc On Sex Hormonal Concentrationscontrasting
confidence: 48%
“…Several studies (14)(15)(16) have examined the effect of exogenous progestogens on IGF-1 levels. The most recent study found that, when used in combination with oral or transdermal oestrogen, the more androgenic progestogens resulted in either no reduction of IGF-1 levels with oral oestrogen or an actual increase in IGF-1 levels with transdermal oestrogen (16). This suggests that oral progesterone, at least in its most androgenic form, may increase GH sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Small intervention studies (2,3,4,5,6,7,8,9,10) and large cross-sectional studies (11,12,13,14,15) have demonstrated that oral estrogens reduce serum concentrations of total IGF1. These findings have been observed both in menopausal women and in those with hypopituitarism.…”
Section: Introductionmentioning
confidence: 99%